Different patterns of expression of cell cycle control and local invasion-related proteins in oral squamous cell carcinoma affecting young patients - Galvis, Marisol Miranda; Santos-Silva, Alan Roger; Jardim, Juscelino Freitas; Fonseca, Felipe Paiva; Lopes, Marcio A.; Almeida, Oslei Paes de; Lopes Pinto, Clovis A.; Kaminagakura, Estela [UNESP]; Sawazaki-Calone, Iris; Speight, Paul M.; Kowalski, Luiz Paulo (Wiley-Blackwell, 2018)
ObjectivesOral squamous cell carcinoma (OSCC) predominantly affects males in the fifth decade of life; nevertheless, an increased incidence in young patients has been reported worldwide, and the clinical and behavioral characteristics of tumors in this group are controversial, and the literature shows divergent results. PurposeTo investigate the clinicopathological features and prognostic significance of the immunoexpression of cell cycle and local invasion proteins in OSCC affecting young patients (40years old). MethodsA tissue microarray was performed with 132 OSCC samples (61 cases of young patients vs 71 cases of elderly patients) and submitted to immunohistochemical reactions with Ki67, p53, p16, Bcl-2, Cyclin D1, C-ErbB2, p21, Myc, EGFR, MMP-9, SMA, Cathepsin K and FGF-2 antibodies. ResultsClinicopathological features and survival rates were similar in both groups. Although overexpression of EGFR (P=.042) and MMP-9 (P=.001) was more frequent in young patients, only C-ErbB-2 (P=.048) and SMA (P=.048) expression correlated with lower disease-free survival (DFS) in this group of patients. ConclusionClinicopathological features and survival rates are similar between younger and older patients with OSCC. The different patterns of C-ErbB2, EGFR, MMP-9, and SMA expression between the groups merits further investigation to understand their role in the early tumor onset in young patients.
Keywords: cell cycle proteins; clinicopathologic characteristics; local invasion proteins; oral squamous cell carcinoma